Gamma‐secretase complex‐dependent intramembrane proteolysis of CD147 regulates the Notch1 signaling pathway in hepatocellular carcinoma. Issue 2 (6th August 2019) - Yong, Yu‐Le; Zhang, Ren‐Yu; Liu, Ze‐Kun; Wei, Ding; Shang, Yu‐Kui; Wu, Jiao; Zhang, Zhi‐Yun; Li, Can; Chen, Zhi‐Nan; Bian, Huijie
Abstract: The γ‐secretase complex is a presenilin‐dependent aspartyl protease involved in the intramembranous cleavage of various type I transmembrane proteins. As a type I transmembrane protein, CD147 is highly expressed in hepatoma cells and promotes cell proliferation, migration, and invasion. However, the direct underlying mechanism of how CD147 promotes cancer cell proliferation is unknown. Here, we demonstrated that CD147 undergoes an intramembranous cleavage by the γ‐secretase at lysine 231 to release its intracellular domains (ICDs). The nuclear translocation of the CD147ICD regulated Notch1 expression by directly binding to the NOTCH1 promoter and promoted the activation of the Notch signaling pathway. Simultaneously, overexpression of CD147ICD promoted cancer cell proliferation via Notch1 signaling. In 102 cases of human hepatocellular carcinoma (HCC) tissues, patients with a high positive rate of nuclear CD147ICD expression had a significantly poor overall survival compared with patients with a low positive rate of nuclear CD147ICD expression. We confirmed that nuclear CD147ICD predicted a poor prognosis in human HCC. The combined therapy of the γ‐secretase complex inhibitor and CD147‐directed antibody showed better efficacy than monotherapy in orthotopic transplantation HCC mouse models. In conclusion, CD147 is cleaved by the γ‐secretase and releases CD147ICD to the cell nucleus, promoting Notch1 expression via direct binding to the NOTCH1 promoter. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.